Characteristics of the classification of quality management companies with requirements of international standards - Тріщ, Галина Михайлівна; Горбенко, Наталія Андріївна; Катрич, Олег Олександрович (Technology audit and production reserves, 2013)
This article refers to the field of quality management. An important task of a modern company is to find models of assessing ability of the quality management system to adapt quickly to the changing economic environment and the social environment. The main aim of this article is to review various types of approaches to the quality management. In general, the systems are diverse by classes; they differ in their structure, types of bonds and the level of control. Therefore, the Quality Management System is researched according to the classification of systems. In this article the Quality Management System is evaluated according to the system and process approach.